The structure at 2.5 Å resolution of human basophilic leukemia-expressed protein BLES03 - Bitto, Eduard (International Union of Crystallography, 2005)
The crystal structure of the human basophilic leukemia-expressed protein (BLES03, p5326, Hs.433573) was determined by single-wavelength anomalous diffraction and refined to an R factor of 18.8% (R (free) = 24.5%) at 2.5 Å resolution. BLES03 shows no detectable sequence similarity to any functionally characterized proteins using state-of-the-art sequence-comparison tools. The structure of BLES03 adopts a fold similar to that of eukaryotic transcription initiation factor 4E (eIF4E), a protein involved in the recognition of the cap structure of eukaryotic mRNA. In addition to fold similarity, the electrostatic surface potentials of BLES03 and eIF4E show a clear conservation of basic and acidic patches. In the crystal lattice, the acidic amino-terminal helices of BLES03 monomers are bound within the basic cavity of symmetry-related monomers in a manner analogous to the binding of mRNA by eIF4E. Interestingly, the gene locus encoding BLES03 is located between genes encoding the proteins DRAP1 and FOSL1, both of which are involved in transcription initiation. It is hypothesized that BLES03 itself may be involved in a biochemical process that requires recognition of nucleic acids.